RELATO DE EXPERIÊNCIA: NO INTERIOR, AS BRINCADEIRAS AINDA “REINAM”. REPORT OF EXPERIENCE : ON THE INSIDE, PLAYING STILL " REIGNS " . - Silva, Maria Zaine de Albuquerque; da Silva, Adriane Corrêa (South American Journal of Basic Education, Technical and Technological, 2014)
RESUMO O brincar é uma atividade humana criadora, na qual a imaginação, fantasia e realidade interagem e integram a produção de novas possibilidades de interpretação, de expressão, de ação pelas crianças, possibilitando o surgimento de relações sociais com outras crianças e adultos. O presente artigo tem por objetivo, mostrar a importância da criança em ter um espaço livre para suas brincadeiras. Palavras-Chave: Relato de Experiência. Brincar. Crianças. ABSTRACT Playing is a creative human activity, in which the imagination, fantasy and reality interact and integrate the production of new possibilities for interpretation, expression, action by children, allowing the emergence of social relationships with other children and adults. The aim’s article is to show the importance of the child to have a free space for their plays. Key -Words: Experience Report. Play. Children.